La pensión alimenticia como derecho fundamental de los menores que se encuentran en periodo de lactancia. - León Vargas, Jaime Israel (Machala : Universidad Técnica de Machala., 2018)
Para obtener el beneficio de percibir alimentos tal como lo establece el Artículo innumerado 2(126) del Código de Niñez y Adolescencia, frente a un criterio del demandado, supuesto padre que menciona que él ya se encuentra demandado y actualmente está pasando una pensión de alimentos para su hijo de nombre Tomas, consecuencia de esto solicita a la autoridad competente que al tratarse de una demanda que se he presentado en su contra, se basa rotundamente a que es por el mismo niño, por tanto en posición de demandado requiere que se archive la causa. En el desarrollo del siguiente trabajo se podrá observar mediante el marco teórico que hablara sobre la conceptualización, la naturaleza jurídica, cuáles son los obligados a pasar y percibir alimentos y cuáles fueron las pruebas que motivaron y determinar que se trataba de un segundo hijo. Así mismo se pondrá en conocimiento de la importancia y cuidado que genera un niño menor o recién nacido a diferencia de otro que tiene cinco años de edad. De igual manera se analizará la importancia de la leche materna para los niños que se encuentran en este periodo de lactancia, obstante a ello considerar si la madre aún está a tiempo para que pueda iniciar una acción de ayuda prenatal.
To obtain the benefit of receiving food as established in Article number 2 (126) of the Code of Children and Adolescents, against a criterion of the defendant, alleged father who mentions that he is already sued and is currently passing a food pension For your child, as a consequence of this, you ask the competent authority that, when dealing with a lawsuit that has been filed against you, it is firmly based on the fact that it is for the same child, therefore, the defendant requires that the case be filed. In the development of the following work can be observed through the development that will talk about the conceptualization, the legal nature, which are those forced to pass and receive food and what were the tests that motivated and determine that it was a second child. Likewise, the importance and care generated by a minor or newborn child, as opposed to another one who is five years old, will be made known. Likewise, the importance of breast milk for children who are in this period of breastfeeding will be analyzed, although to consider whether the mother is still in time so that she can initiate an action of prenatal help. As a conclusion of the work, it is carried out by comparing the reactive with the development of the work, where we can find all the necessary information for the food pension and analyzing the important points that the Childhood and Adolescence Code establishes in accordance with what establishes the constitution of the Republic will be able to verify what is the reality of what happens in the case of this action presented by Mrs. Juana Rigoberta Morán, always taking as a point to highlight the best interests of the child, in the face of any adversity, since the law aforementioned protects it.
Keywords: PENSION; ARCHIVAR CAUSA; ALIMENTO